ANALISIS BUKU “WHAT’S SO WRONG ABOUT YOUR SELF HEALING” DALAM PENERAPAN NILAI-NILAI SELF ACCEPTANCE - Rianty, Refina Okta; Yulia, Cici; Rahmah, Alyana Maulia; Rahmadina, Oktavia; Fajria, Fajria; Rahman, Alya Nur; Kirani, Putri Balqis (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2024)
Abstract: This research aims to provide information about the values of Self Acceptend contained in the book entitled